[Au(S–C6F5)] and [Au(S–C6F4–CF3)]: Reactivity, Structure, DSC, and Calculation Studies - Tkachenko P. Pavel; Maksimov A. M. Aleksandr Mikhaylovich; Sinitsa V. Varvara; Sulyaeva V. S. Veronica; Pishchur D. A. Denis; Plyusnin P. E. Pavel; Berezin A. S. Aleksey Sergeevich; Sukhikh T. S. Taisiya; Sokolov M. N. Maxim; Abramov P. A. Pavel Aleksandrovich (2025, 2025)
Title screen